DOES PROFESSIONAL AUTONOMY PROTECT MEDICAL FUTILITY JUDGMENTS? - Gampel, Eric (Bioethics, 2006)
Despite substantial controversy, the use of futility judgments in medicine is quite common, and has been backed by the implementation of hospital policies and professional guidelines on medical futility. The controversy arises when health care professionals (HCPs) consider a treatment futile which patients or families believe to be worthwhile: should HCPs be free to refuse treatments in such a case, or be required to provide them? Most physicians seem convinced that professional autonomy protects them from being forced to provide treatments they judge medically futile, given the lack of patient benefit as well as the waste of medical resources involved. The argument from professional autonomy has been presented in a number of articles, but it has not been subjected to much critical scrutiny. In this paper I distinguish three versions of the argument: 1) that each physician should be free to exercise his or her own medical judgment; 2) that the medical profession as a whole may provide futility standards to govern the practice of its members; and 3) that the moral integrity of each physician serves as a limit to treatment demands. I maintain that none of these versions succeeds in overcoming the standard objection that futility determinations involve value judgments best left to the patients, their designated surrogates, or their families. Nor do resource considerations change this fact, since they should not influence the properly patient-centered judgment about futility.